2021
DOI: 10.1681/asn.2021010059
|View full text |Cite
|
Sign up to set email alerts
|

High SARS-CoV-2 Viral Load in Urine Sediment Correlates with Acute Kidney Injury and Poor COVID-19 Outcome

Abstract: BackgroundAcute kidney injury (AKI) is a complication of coronavirus disease 2019 (COVID-19) that is associated with high mortality. Despite documented kidney tropism of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), there are no consistent reports of viral detection in urine or correlation with AKI or COVID-19 severity. Here we hypothesize that quantification of SARS-CoV-2 viral load in urine sediment from COVID-19 patients correlates with occurrence of AKI and mortality. MethodsSARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
(155 reference statements)
2
25
1
Order By: Relevance
“…This is supported by the finding that urinary SARS‐CoV‐2 and SARS‐CoV‐2 N protein can be detected in COVID‐19 patients with AKI and correlate with the AKI severity and mortality. [ 41 , 42 ] These clinical observations suggest the pathogenic role for SARS‐CoV‐2 N in AKI. Findings from the present study confirmed that this clinical notion unraveled the new role for SARS‐CoV‐2 N protein in the pathogenesis of AKI.…”
Section: Discussionmentioning
confidence: 95%
“…This is supported by the finding that urinary SARS‐CoV‐2 and SARS‐CoV‐2 N protein can be detected in COVID‐19 patients with AKI and correlate with the AKI severity and mortality. [ 41 , 42 ] These clinical observations suggest the pathogenic role for SARS‐CoV‐2 N in AKI. Findings from the present study confirmed that this clinical notion unraveled the new role for SARS‐CoV‐2 N protein in the pathogenesis of AKI.…”
Section: Discussionmentioning
confidence: 95%
“…ACE2 is strongly expressed in kidney tubules [87,129,130]; SARS-CoV-2 can be detected in urine [131] and in autopsy kidney tissue from SARS-CoV-2-infected patients [132,133], and COVID-19 patients show signs of kidney damage [71,134,135]. To determine if the kidney function decline reported for COVID-19 patients could be due to the infection of kidney cells by SARS-CoV-2, hES-derived kidney epithelium organoids were interrogated.…”
Section: Kidneymentioning
confidence: 99%
“…Severe COVID-19 disease is in fact frequently associated with kidney injury produced by both indirect mechanisms and direct damage due to virus replication [27,28]. Actually, SARS-CoV-2 has been found in autopsy specimens and urine samples [29,30], and its cellular receptor, ACE2, is highly expressed in renal tubules [31].…”
Section: Meds433 Affects Sars-cov-2 Replication In Kidney Organoidsmentioning
confidence: 99%